2018
DOI: 10.2136/vzj2018.06.0119
|View full text |Cite
|
Sign up to set email alerts
|

Localized Sulfide Oxidation Limited by Oxygen Supply in a Full‐Scale Waste‐Rock Pile

Abstract: Open-pit mines produce large amounts of waste rock that is placed on-site, often in tall, mixed-composition piles. These waste-rock piles pose environmental risks because their weathering (i.e., sulfide oxidation) may generate acidic and metalladen drainage. However, the reaction and transport limitations controlling sulfide oxidation remain poorly described at field scales. Here, we present comprehensive multiyear data from two instrumented boreholes in an operational waste-rock pile at the Antamina mine in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…In a minority of field barrels bearing intrusive PAG waste rock with NPR < 1 (3 out of 49 barrels), drainage pH values reached pH < 3 after 5–10 years (Figure 2). The observed release of elevated sulfate and metals such as Fe, Cu, or Zn (concentrations >100 mg/L; Figure S2) from PAG compared to NAG waste rock (concentrations <1 mg/L) aligns with previous research at Antamina 2,52,54,55 and the general notion that weathering of predominantly high-sulfide, low-carbonate waste rock can generate acidic drainage conditions that mobilizes sulfate and metals at high levels. 1,5…”
Section: Resultssupporting
confidence: 87%
“…In a minority of field barrels bearing intrusive PAG waste rock with NPR < 1 (3 out of 49 barrels), drainage pH values reached pH < 3 after 5–10 years (Figure 2). The observed release of elevated sulfate and metals such as Fe, Cu, or Zn (concentrations >100 mg/L; Figure S2) from PAG compared to NAG waste rock (concentrations <1 mg/L) aligns with previous research at Antamina 2,52,54,55 and the general notion that weathering of predominantly high-sulfide, low-carbonate waste rock can generate acidic drainage conditions that mobilizes sulfate and metals at high levels. 1,5…”
Section: Resultssupporting
confidence: 87%
“…As a result, sulfide oxidation and bulk weathering rates reported from laboratory and field experiments vary by orders-of-magnitude across sites (Table 3). Because it is virtually impossible to resolve all molecular-scale mineralogical heterogeneity, waste-rock reactivity or weathering rates are typically presented through representative bulk parameters such as drainage loads (i.e., net sulfate leaching) or oxygen consumption or heat production rates [192][193][194]. Similarly, the estimation of the acid-producing versus acid-neutralizing nature of waste-rock material is often based on bulk laboratory tests (static testing or acid-base accounting (ABA)) rather than (or complementary to) microscale mineralogical analyses.…”
Section: Characterization Of Bulk Waste-rock Reactivitymentioning
confidence: 99%
“…In addition to diffusion, pressure gradients can result in advective gas transport in porous media [263]. Estimates of advective gas transport using e.g., pneumatic heads and Darcy's law for gas, have shown that barometric fluctuations can be relevant for gas transport particularly through more permeable coarse rubble zones at the bases of waste-rock piles [194,243,264,265].…”
Section: Gas Transportmentioning
confidence: 99%
See 2 more Smart Citations